Revolaks - Forstén, Lennart (1845)
Helsingfors : A.W. Gröndahl & A.C. Öhman 1845 : Dresden, Alder u. Dietze
Keywords: maisema - Revonlahti - 1800-luku; maaseutu; vesistöt - Siikajoki; kirkot - Revonlahti - 1800-luku; Revonlahti - 1800-luku